Spatial and temporal transcriptomics of Schistosoma japonicum‐induced hepatic granuloma formation reveals novel roles for neutrophils. Issue 2 (24th May 2013) - Chuah, Candy; Jones, Malcolm K.; Burke, Melissa L.; Owen, Helen C.; Anthony, Barrie J.; McManus, Donald P.; Ramm, Grant A.; Gobert, Geoffrey N.
Abstract : A novel dual role for neutrophils in the mediation of tissue damage and repair in Schistosoma japonicum egg‐induced hepatic granulomatous lesions. Abstract : The severity of schistosome egg‐induced hepatic granulomatous pathology depends markedly on the nature of the host immune responses. In this study, we used LMM and microarray analysis to compare gene expression profiles of histologically distinct zones within, and directly proximal to, hepatic granulomas that developed in C57BL/6 mice infected with Schistosoma japonicum . There was significant up‐regulation of type‐1, type‐2, and type‐17 immune‐associated genes within the granuloma core (adjacent to eggs), followed by increased expression of type‐2 and fibrotic genes at the outer zones of granulomas. Neutrophil‐associated genes were also found to be expressed differentially in the core and at the peripheral zone of granulomas, present at 7 weeks p.i., demonstrating a significant role of neutrophils in S. japonicum granulomatous pathology. The release of NETs was observed microscopically in granulomas obtained from the livers of infected mice and when human neutrophils were incubated in vitro in the presence of S. japonicum eggs. These finding are the first to suggest a novel, dual role for neutrophils in the mediation of tissue damage and repair in S. japonicum egg‐induced hepatic granulomatous lesions. Together, these results provide an overview of the local events occurring within the granuloma microenvironment.